2015
DOI: 10.1002/2014jb011516
|View full text |Cite
|
Sign up to set email alerts
|

Crustal and upper mantle velocity structure in the vicinity of the eastern Tennessee seismic zone based upon radial P wave transfer functions

Abstract: Teleseismic transfer function analysis is used to investigate crust and upper mantle velocity structure in the vicinity of the active eastern Tennessee seismic zone (ETSZ). The ETSZ is associated with the New York-Alabama (NY-AL) magnetic lineament, a prominent aeromagnetic anomaly indicative of Grenville-age, basement structure. Radial component, P wave transfer functions for 10 short-period stations operated by the Center for Earthquake Research and Information are inverted for velocity structure. Velocity p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Over this length scale, Moho depth varies by less than 3–4 km in the plane‐normal direction, with a maximum plane‐normal dip of <3° for the D line [ Parker et al, ]. In addition, the presence of the Moho waning in both W and D line inversions and the apparent absence of a Moho velocity increase in nearby single station analyses [ Graw et al, ] add confidence. Small‐scale reductions in apparent Moho amplitude on the W line correlate with lower station density (e.g., ~255 km and ~305 km, Figure ), and the continuity of the Moho in the PPs individual mode inversion (Figure S5b) indicates that these are probably not real structures.…”
Section: Observed Discontinuitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Over this length scale, Moho depth varies by less than 3–4 km in the plane‐normal direction, with a maximum plane‐normal dip of <3° for the D line [ Parker et al, ]. In addition, the presence of the Moho waning in both W and D line inversions and the apparent absence of a Moho velocity increase in nearby single station analyses [ Graw et al, ] add confidence. Small‐scale reductions in apparent Moho amplitude on the W line correlate with lower station density (e.g., ~255 km and ~305 km, Figure ), and the continuity of the Moho in the PPs individual mode inversion (Figure S5b) indicates that these are probably not real structures.…”
Section: Observed Discontinuitiesmentioning
confidence: 99%
“…A reduction of Moho amplitude appears not only in this study beneath the Blue Ridge province but also as a more complete loss of Moho amplitude below nearby stations [ Graw et al, ] and in a zone straddling the Blue Ridge Escarpment that lies ~200 km to the northeast [ Wagner et al, ]. A weak Moho velocity contrast in the general area of this study is also reported in a continent‐scale joint inversion of Ps receiver function and surface wave data, although the Moho anomalies are not correlated in detail [ Shen and Ritzwoller , ].…”
Section: Moho Strength Variation Beneath the Southern Appalachiansmentioning
confidence: 99%
See 1 more Smart Citation
“…S2), which is < 2 km in this area [Brandmayr and Vlahovic, 2016]. This area of complex geologic features likely hosts terrains accreted during the Iapetus subduction and rich in metasedimentary rocks [Graw et al, 2015].…”
Section: Discussionmentioning
confidence: 87%
“…We tend to rule out this possibility since this effect should be systematic, but no or little overestimation occurred in the Cumberland Plateau, Blue Ridge, Piedmont, and Coastal Plain. Mooney and Kaban [2010] report a sedimentary cover thickness of about 6 km beneath the Valley and Ridge, and Graw et al [2015] estimated, using receiver functions, V P < km/s down to 8-10 km of the depth along the NY-AL lineament. These values are within the range of our estimate, although Graw et al [2015] interpret their findings as low velocity basement crust, which is consistent with previous studies that estimated a shallower sedimentary cover in the area [Sodbinow and Bollinger, 1978;Owens et al, 1984].…”
Section: Resultsmentioning
confidence: 99%